Design and manufacturing of a cylinder head by laser powder bed fusion. Issue 1 (February 2021) - Willkomm, J; Kuhlbach, K; Merget, D; Wagner, M; Reich, S; Ziegler, S; Schleifenbaum, J H
Abstract: Nowadays the reduction of fuel consumption is the most important challenge for engine development. Laser Powder Bed Fusion (LPBF) as an additive manufacturing process with its implied design freedom makes it possible to reduce combustion emissions, increase engine efficiency and respond specifically to customer requirements. In this work, the outstanding degree of freedom of LPBF is exploited for a new design concept for a cylinder head of an engine in automotive industry in order to address further reduction of fuel consumption through improved cooling performance. Within the given installation space and under consideration of the existing mounting and connection positions, the design concept was developed, subsequently manufactured and reworked. In order to develop a design that meets the LPBF requirements, both the potential of the LPBF using the geometric degrees of freedom as effectively as possible and the limitations are considered. The opposing design drivers between exploitation of potentials and limitations in LPBF are achieved by an iterative design process supported by an own developed design tool. With the new design concept, a reduction of the metal temperature in the cylinder head of approx. 25 K is achieved, verified by simulation.